2022
DOI: 10.47102/annals-acadmedsg.2022203
|View full text |Cite
|
Sign up to set email alerts
|

Sex and ethnicity modified high 1-year mortality in patients in Singapore with newly diagnosed atrial fibrillation

Abstract: Introduction: We investigated sex and ethnic differences in the incidence, clinical characteristics and 1-year mortality of patients with newly diagnosed AF in a multi-ethnic population. Method: This retrospective cohort study of patients diagnosed with AF from 2008 to 2015 was based on medical claims, casemix and subvention data submitted to the Ministry of Health. Patients with AF were matched with controls without AF for age (3-year bands), sex and ethnicity, and categorised as middle-aged (45–64 years) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless, based on the APC model, we found a greater downward trend or smaller upward trend of AF/AFL-related deaths among women across SDI quintiles, except for low-and high-SDI countries, indicating that the focus on women's health has been effective over the past few decades. In a national study in Singapore, men had 17% increased odds of mortality compared to women one year after a diagnosis of AF/ AFL [22]. The high level of inclusive medical care in countries with a high SDI and the low-quality medical care in countries with a low SDI contributed to sex-homogeneous treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, based on the APC model, we found a greater downward trend or smaller upward trend of AF/AFL-related deaths among women across SDI quintiles, except for low-and high-SDI countries, indicating that the focus on women's health has been effective over the past few decades. In a national study in Singapore, men had 17% increased odds of mortality compared to women one year after a diagnosis of AF/ AFL [22]. The high level of inclusive medical care in countries with a high SDI and the low-quality medical care in countries with a low SDI contributed to sex-homogeneous treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this issue of the Annals, Tan et al had taken further steps to illustrate the interesting differences in the mortality and incidences in multiethnic Singapore. 6 Albeit the study was retrospective in nature with its limitations and potential unknown confounding variables, the authors ought to be commended on several pertinent observations. Firstly, the study was consistent with the huge prospective observational study, Global Anticoagulant Registry in the Field (GARFIELD-AF) 7 and demonstrated incremental mortality among newly diagnosed AF patients belonging to the 3 main ethnic groups (Chinese, Malays and Indians) in Singapore.…”
mentioning
confidence: 99%